HUMAN RESOURCE MANAGEMENT PRACTICES OF EMPLOYEE RETENTION IN RESEARCH UNIVERSITIES IN ISRAEL - Harpaz, Amir (Digital Repository of Theses - SSBM Geneva, 2023)
Higher education systems, and universities among them, are experiencing high competition in recent years in retaining their employees. Universities are facing challenges from other competitive markets and the private sector. Failure to address and resolve retention issues can cause short- and long-term impacts on the organization’s performance. There is a lack of empirical data regarding Human Resource Management (HRM) strategies, perspectives, practices, and their effects on employee retention within universities in general and in Israel. This lack of data and understanding contributes to employee turnover. To date, no comprehensive, in-depth research has been conducted on the reasons for administrative staff turnover in universities in Israel.